So help me Todd. The final season [videorecording (DVD)] - Prendergast, Scott; Cadrot, Thomas; Harden, Marcia Gay; Astin, Skylar, 1987-; Wise, Madeline (Freestyle Digital Media, 2024)
In the Final Season, successful lawyer Margaret Wright finally becomes a partner in her firm while her son, Todd, establishes his in-house private investigator service and takes on more cases outside the firm. Struggling to keep the firm afloat as it faces financial ruin, Margaret must take on new clients, keep collectors at bay, and continue collaborating with Todd to solve her current cases. The 2-disc collection includes every hilarious episode, exclusive deleted scenes and a gag reel!